The Complementary Relationship between the Legal and Customary Rules of Aflaj in the Sultanate of Oman - A Comparative Study – - Al-Khamisi, Khalid Abdullah Khamis; Al-Shuaili, Mohamed Saif Duwaim (Journal of Ecohumanism, 2024)
Resorting to adopting interdisciplinary studies has become urgent in light of the rapid developments in various aspects of life in the world, including social, economic, cultural and others, in addition to the legislative and regulatory vacuum for some sectors and services, especially those that depend on the prevailing societal norms in each environment and society, based on the sovereignty of those norms in families, organizations and societies. Among the sectors that are linked to the fabric of life in the Sultanate of Oman is Aflaj system, which is considered the first water resource in terms of economic, social and livelihood importance in the Sultanate. The governing norms for regulating the exploitation of this resource in the Sultanate have varied according to what is palatable to villages and countries, as attention to it in Omani jurisprudential encyclopedias was clearly evident. In light of the modern legal legislation in the Sultanate regulating this resource, there seems to be a need to shed light and demonstrate the cognitive integration between theoretical aspects, judicial applications, and established norms in this regard, while clarifying the important relationship of the type of legal research methods appropriate in the production of this study; As an picture and manifestation of interdisciplinary studies between law and other sciences, we ask Allah for success and guidance.